Resilient Parents… Resilient Communities: A Pilot Study Trialing the Bounce Back and Thrive! Resilience-Training Program With Military Families - Mikolas, Cynthia; Pike, Ashley; Jones, Chelsea; Smith-MacDonald, Lorraine; Lee, Melina; Winfield, Hope; Griffiths, Jennifer; Perry, Ryan; Olson, David M.; Heber, Alexandra; Olson, Joanne; Sevigny, Phillip R.; et al. (Frontiers in Psychology, 2021)
Introduction The resilience of Canadian military families (CMFs) – the main support of the Canadian Armed Forces service members (SMs) – is imperative. The Canadian Armed Forces aims to ensure that SMs and their families are resilient and SMs ready to respond when called upon for combat, peacekeeping or pandemic/disaster-response. Family concerns, however, can realistically distract SMs from the mission, potentially compromising themselves, their unit and the mission. Resilience-training programs such as Bounce Back and Thrive! (BBT) can help families manage the realities of military life. Objective This pilot study aimed to evaluate suitability of BBT implementation by Military Family Resource Centers (MFRCs), including whether BBT: (1) fosters resilience-building among parents, (2) facilitates CMF resilience-building, (3) can be contextualized for CMFs, and (4) supports MFRCs in cultivating a culture of resilience. Methods An exploratory qualitative design was used. BBT was offered to parents face-to-face. Participants completed focus groups after the first 6 sessions, final 4 sessions, and one-year post-intervention. Data was thematically analyzed. Results Nine military parents participated. Four major themes resulted: (1) military parent resilience-building, (2) CMF resilience-building, (3) BBT program feedback and contextualization, and (4) MFRCs as community resilience hubs. Discussion BBT enabled parents to gain a new perspective on resilience, engage in dialogue and intentionally role model resilience skills. Military-specific BBT contextualization and online-delivery formats would increase suitability and access for CMFs. Access to resilience programs delivered through MFRCs would support CMFs. Further research is warranted.